A linear, low power, 2.5-dB NF LNA for UWB application in a 0.18 μm CMOS. Issue 12 (December 2015) - Mohammadi, Ismail; Sahafi, Ali; Sobhi, Jafar; Daei Koozehkanani, Ziaddin
Abstract: This paper presents an ultra-wideband common-gate low-noise amplifier (UWB CG-LNA) that employs negative feedback to overcome the trade-off that exists between noise and input impedance matching while preserving linearity, stability, and low power operation. The proposed LNA has been designed and simulated via TSMC 0.18-μm CMOS. UWB LNA operates from 3.1 to 10.1 GHz. Designed LNA consumes 2.3 mA from a 1.8-V supply. Post-layout simulation shows that LNA achieves a maximum voltage gain of 13.7 dB, a minimum noise figure of 2.5 dB, better than − 10 dB S 11 and + 4.5 to + 9.5 dBm IIP3 across the entire bandwidth. The Volterra series has been used to analyze the linearity of circuit.